Gasoline Engine Fuel Pump Pressure Nonlinear Function Fuzzy Control - Junyan XU; Jianrong BO; Zhuangwen WU (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to improve the accuracy of electronic fuel injection (EFI) engine fuel pump pressure, according to the characteristics of pump directly driven by motor, a nonlinear mathematical model is built for the fuel supply system of EFI engine pressure control. And then, the nonlinear-function-optimized flow signal is introduced to adjust the parameters of nonlinear function. With the PI control algorithm, the precise tracking control of injection pressure is achieved. The simulation and experiment results show that, it can indirectly realize from the speed control to pressure control. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4220